1996
DOI: 10.1021/jo960216c
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition of Malonate Anions to Prochiral Acceptors Catalyzed by l-Proline Rubidium Salt

Abstract: l-Proline rubidium salt catalyzes the asymmetric Michael addition of malonate anions to prochiral enones and enals. This method can be applied to a wide range of substrates to give adducts with a predictable absolute configuration:  (S)-adducts from (E)-enones/enals and (R)-adducts from cyclic (Z)-enones. Both the secondary amine moiety and the carboxylate moiety are critical for the catalytic activity and asymmetric induction. Varying the countercation also affects the reaction course. High enantiomeric exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(60 citation statements)
references
References 42 publications
1
56
0
3
Order By: Relevance
“…Yamaguchi group's pioneering work in the 1990s introduced L-proline rubidium salt as a catalyst for the addition of diisopropyl and di-tert-butyl malonates to cyclic enones with low to good enantioselectivities (35-88% ee) [17,18]. Then List and co-workers treated a mixture of acetone and L-proline (35 mol %) in DMSO with cyclohex-2-en-1-one [19].…”
Section: Malonates and Related 13-dicarbonylsmentioning
confidence: 99%
“…Yamaguchi group's pioneering work in the 1990s introduced L-proline rubidium salt as a catalyst for the addition of diisopropyl and di-tert-butyl malonates to cyclic enones with low to good enantioselectivities (35-88% ee) [17,18]. Then List and co-workers treated a mixture of acetone and L-proline (35 mol %) in DMSO with cyclohex-2-en-1-one [19].…”
Section: Malonates and Related 13-dicarbonylsmentioning
confidence: 99%
“…1,2 L-Proline catalyzes the Michael reaction of ketones with nitro olefins to provide a variety of chiral Michael addition products. [6][7][8][9] This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Abstractsmentioning
confidence: 99%
“…2 As pioneering works in this reaction with organocatalysis, a rubidium salt of L-proline and a chiral (2-pyrrolidyl)alkyl ammonium hydroxide were discovered as effective catalysts for the asymmetric Michael addition of malonates to enones by Yamaguchi 3 and Taguchi, 4 respectively, in the early 1990s. Since Michael addition reaction of malonates to enones provides 1,5-ketoesters, which are synthetically useful substrates, there is much interest in the development of new chiral organocatalysts for this reaction and elucidation of their reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Since Michael addition reaction of malonates to enones provides 1,5-ketoesters, which are synthetically useful substrates, there is much interest in the development of new chiral organocatalysts for this reaction and elucidation of their reaction mechanisms. 1,2,5 We recently reported that a primary β-amino acid salt, O-TBDPS β-homoserine lithium salt (1), was an effective catalyst for the Michael addition reaction of dimethyl malonate (2) to 2-cyclohexen-1-one (3) and that the β-amino acid moiety was necessary for obtaining Michael adduct 4 with high enantioselectivity, since α-and γ-amino acid salt analogues 5 and 6 resulted in lower enantioselectivity than that from using the β-amino acid salt catalyst 1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%